Single‐Molecule Fluorescence Enhancement by Plasmonic Core–Shell Nanostructures Incorporating Nonlocal Effects. Issue 5 (20th February 2022) - Kupresak, Mario; Zheng, Xuezhi; Mittra, Raj; Sipus, Zvonimir; Vandenbosch, Guy A. E.; Moshchalkov, Victor V.
Abstract: Molecular fluorescence may strongly be affected by plasmonic environments, especially the ones with deep‐nanometer features, associated with the emergence of nonclassical effects. Such effects are largely investigated by a nonlocal hydrodynamic model with additional boundary conditions, describing the collective motion of the free electron gas in metals. The study of a fluorophore in the presence of the nano core–shell topology is performed, by employing the following models: the hard‐wall hydrodynamic model and the generalized nonlocal optical response. The analysis is conducted by investigating the fluorescence rates of the system, while considering the fluorophore located inside and outside the nanoparticle. It is demonstrated that the rates generated by the above models may considerably differ from the ones obtained via the classical approach. The optimal fluorescence enhancements for different size and material parameters are found both inside and outside the studied topology. Abstract : The study of a fluorescent molecule in the presence of plasmonic core–shell nanoparticles, with nonlocal material parameters, is conducted. The fluorescence enhancement of the system is investigated, considering the molecule both inside and outside the nanoparticles. The impact of the nonlocal response models on the studied feature is analyzed.